Prevalence and Morphology of the Coracoclavicular Joint: An Osteological Study of 2,724 Subjects Using Univariable and Multivariable Logistic Regression Analyses - Harlow, Ethan Robert; Sasala, Lee M.; Talbot, Christopher E.; Desai, Bijal J.; Ina, Jason; Miskovsky, Shana (Frontiers in Surgery, 2021)
Abstract Background: The coracoclavicular joint (CCJ) is an anomalous articulation between the surfaces of the inferior clavicle and superior coracoid and its etiology is controversial. Reportedly, symptomatic patients demonstrate significant functional limitations including shoulder abduction loss and potential for brachial plexus compression and impingement. Purpose: To determine the prevalence of CCJ across age, gender and ethnicity, and to identify clinically useful morphological characteristics. Methods: 2724 subjects with intact clavicles and scapulae from the Hamann-Todd Osteological Collection were evaluated for the presence of CCJ. Logistic regression was used to determine the effect of age, height, gender, and race on prevalence of CCJ. 354 clavicles with CCJ were measured for size and location of the CCJ facet. Results: CCJ was observed in 9% of subjects. CCJ was more prevalent in African-Americans (12%) than Caucasian-Americans (6%) (p<0.001) and more prevalent in females (11%) than males (8%) (p=0.055). Facet location along clavicle length was consistent (average 25%, range 15-35%). But, facet location along clavicle width varied (average 60%, range 10-90%), with males having a more posterior location. For every 10-year increase in age, facet elevation (p=0.001) and surface area (p<0.001) increased. Conclusions: CCJ prevalence was 9% in our large osseous population, found more commonly in African-Americans and females. Facet location is predictable with respect to clavicle length, but less so along clavicle width. The clavicular facet may develop at some point in life and continue to grow in size after its appearance. Clinical Relevance: Presence of a CCJ represents a potential overlooked source of anterior shoulder pain and supracoracoid impingement. Epidemiologic and morphological characteristics presented in our study can aid in the identification, clinical understanding, and surgical excision of a symptomatic CCJ. Level of Evidence: Level IV Keywords: Coracoclavicular joint, shoulder impingement, clavicle, scapula, osteological, musculoskeletal abnormalities, population variation, shoulder